2022
DOI: 10.1155/2022/7390836
|View full text |Cite|
|
Sign up to set email alerts
|

Mobile Terminal Equipment and Methods of Martial Arts Movement Correction in Intelligent Physical Education Environment

Abstract: In recent years, the physical quality of middle school students in China has generally declined, which has attracted the attention of the state and the Ministry of education. With the development of Internet technology, China’s physical education teaching environment has gradually become intelligent. This article mainly studies the mobile terminal equipment and methods of martial arts movement correction in the intelligent physical education environment. 21 young martial arts athletes were selected as the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%